Preventive Measures in Patients with Central Serous Choroidopathy with Optic Disc Hypoplasia - I.R. Asrorkhujaeva; R.R. Asrorkhujaeva; A.R. Zakirxodjayev (Genius Publishing Group, 2023)
Purpose of the study Evaluation of the effectiveness of the method for the prevention of central serous choroidopathies in patients with optic disc pit.
Keywords: Optic Disc Pit; Choroidopathies I